Interactions of light intensity, insecticide concentration, and time on the efficacy of systemic insecticides in suppressing populations of the sweetpotato whitefly (Hemiptera: Aleyrodidae) and the citrus mealybug (Hemiptera: Pseudococcidae) - Cloyd, Raymond A.; Williams, Kimberly A.; Byrne, Frank J.; Kemp, Kenneth E. (My University, 2012)
The impact of light intensity on the uptake and persistence of the systemic neonicotinoid insecticides, imidacloprid and dinotefuran, were evaluated in poinsettia (Euphorbia pulcherrima Willd.) and yellow sage (Lantana camara L.). Insecticide residues were measured in leaves sampled from the treated plants at four time intervals after treatment to determine the relationship between insecticide concentration and efficacy against two insect pests: sweetpotato whitefly, Bemisia tabaci Gennadius, and the citrus mealybug, Planococcus citri Risso. The insecticides were evaluated at their respective label rate and at the comparable label rate of the other insecticide under two different light environments: ambient and shade. The uptake of dinotefuran into yellow sage was more rapid at both treatment rates than both rates of imidacloprid, resulting in higher percent mortality of whitefly nymphs (89.8–100) compared with imidacloprid (14.1–89.2) across all 4 wk. Additionally, plants that received both rates of dinotefuran had fewer whitefly pupae (<1.0) at week 4 compared with imidacloprid-treated plants (23.7–25.3). The uptake of dinotefuran into poinsettia plants was also more rapid and resulted in quicker and higher percent mortality of whitefly nymphs (89.5–99.6) compared with imidacloprid (14.1–89.2) across all 4 wk. However, despite efficient uptake, the efficacy of both systemic insecticides was less for citrus mealybug where percent mortality values were <50% among all the treatments across the 4 wk. The use of the two systemic insecticides evaluated in regards to pest management in horticultural cropping systems is discussed.
Keywords: Greenhouse; Floriculture; Systemic insecticide; Light intensity; Pest management